Mixed methods assessment of women's risk of intimate partner violence in Nepal - Cari Jo Clark; Gemma Ferguson; Binita Shrestha; Prabin Nanicha Shrestha; Brian Batayeh; Irina Bergenfeld; Stella Chang; Susi McGhee (BMC, 2019)
Abstract Background Intimate partner violence (IPV) is a significant public health issue that affects one in three women globally and a similarly large number of women in Nepal. Although important policy and programmatic steps have been taken to address violence against women in Nepal over the past decade, there is still a gap on IPV research in Nepal, particularly with regard to social norms. Methods This mixed-methods study used in-depth interviews with women and their husbands as well as baseline survey data from a cluster randomized trial testing a primary prevention intervention for IPV to examine the prevalence and risk factors for IPV. Baseline survey data included 1800 women from Nawalparasi, Chitwan, and Kapilvastu districts in Nepal. Multivariate regression was used to identify risk and protective factors for exposure to physical and / or sexual IPV in the prior 12 months. Case-based analysis was used to analyze one of 18 pairs of in-depth interviews to examine risk and protective factors within marriages. Results Of 1800 eligible participants, 455 (25.28%) were exposed to IPV. In multivariate analyses, low caste, wife employment, income stress, poor marital communication, quarrelling, husband drunkenness, exposure to IPV as a child, in-law violence, and gender inequitable normative expectations were associated with IPV. The selected case interview represented common themes identified in the analysis including the wife's exposure to violence as a child, husband alcohol use, and marital quarrelling. Conclusions Gender inequitable norms in the community and the intergenerational transmission of attitudes and behaviors supportive of IPV are important to address in intervention measures.